Assessment of Tunnel Explosion Mitigation Techniques for Fire Scenarios Involving Hydrogen Tank Rupture - Volodymyr Shentsov; Luisa Giuliani; Wenqian Liu; Frank Markert (Energies, 2025)
This paper presents a review of explosion mitigation techniques for road tunnels, with a focus on scenarios involving high-pressure hydrogen tank rupture under fire conditions. Both passive and active strategies are considered—including structural configurations (e.g., tunnel branching, vent openings, right-angle bends) and protective systems (e.g., drop-down perforated plates, high-performance fibre-reinforced cementitious composite (HPFRCC) panels)—to reduce blast impact on tunnel occupants and structures. The review highlights that while measures such as blast walls or energy-absorbing barriers can significantly attenuate blast pressures, an integrated approach addressing both blast load reduction and structural resilience is essential. This paper outlines how coupled computational fluid dynamics–finite element method (CFD–FEM) simulations can evaluate these mitigation methods, and we discuss design considerations (e.g., optimising barrier placement and tunnel geometry) for enhanced safety. The findings provide guidance for designing safer hydrogen vehicle tunnels, and they identify gaps for future research, including the need for experimental validation of combined CFD–FEM models in hydrogen fire–explosion scenarios.